Pemberian Ekstrak Daun Kelor Terhadap Kadar Hemoglobin Pada Remaja di SMP Negeri 3 Kediri - Galuh Pradian Yanuaringsih (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Anemia is a nutritional problem that exists in every corner of the world. The prevalence of anemia in adolescents is 27% in developing countries and 6% in developed countries. A preliminary survey conducted at SMP Negeri 3 Kediri on eighth grade female students found that out of 20 students, 10 students, 50% had anemia. The purpose of this study was to determine the effect of Moringa leaf extract on hemoglobin levels in adolescents at SMP Negeri 3 Kediri. This study was a pre-experimental study with a one-group pre-test-post-test design. The population in this study were 30 female adolescents aged 15-18 years at SMP Negeri 3 Kediri City who met the inclusion and exclusion criteria. The research material used was Moringa leaves which are difficult to extract and packaged in 500 mg capsules, which were then given to adolescents with a dose of 2 times a day for 2 consecutive weeks. The tool for measuring hemoglobin levels was Easy Touch. The analysis test used was the Wilcoxon test. The results of the study showed that Ho is rejected and Ha is accepted. So there is an effect of giving Moringa leaf extract (Moringa Oliefera) on increasing hemoglobin levels in female students at SMP Negeri 3 Kediri